A Matlab Algorithm for the Resolution of Fourth Degree Equations - Donato, Alessia (Journal of Mathematical Economics and Finance, 2018)
In this article,  we propose  an algorithm for the resolution of fourth degree equations,  explicitly showing the solution method used, and we compare the results ob- tained with the Matlab “root” command.